Efficacy of Vandetanib in Treating Locally Advanced or Metastatic Medullary Thyroid Carcinoma According to RECIST Criteria: A Systematic Review and Meta-Analysis - Trimboli, Pierpaolo; Castellana, Marco; Virili, Camilla; Giorgino, Francesco; Giovanella, Luca (Frontiers in Endocrinology, 2018)
Background. Vandetanib is the most largely used tyrosine kinase inhibitor (TKI) in patients with locally advanced and/or metastatic medullary thyroid cancer (MTC). Here we conducted a systematic review on its efficacy and attempted to perform a meta-analysis adopting standardized RECIST criteria as end-points. Methods. The terms “medullary thyroid” and “protein kinase inhibitor” (then including all TKIs) were searched in PubMed, ClinicalTrials.gov and CENTRAL. Only original studies reporting the use of Vandetanib as single agent in MTC were included. The last search was performed on October 31, 2017 and registered in PROSPERO on December 12, 2017 (n= CRD42017081537). Results. The search revealed 487 articles, and, after removing duplicates, reading title and abstract, and screening the eligible papers, 10 studied were finally included. Two papers were randomized controlled trials and eight were observational longitudinal studies. No data were available for overall survival. No heterogeneity nor publication bias were recorded in the pooled rate of complete response (0.7%) and stable disease (47%). Mild to moderate heterogeneity were recorded in the pooled rate of other endpoints. Data of the studies did not allow to perform a meta-analysis of time-to-event outcomes. Conclusions. Vandetanib should be considered as a promising treatment in advanced MTC. However, data based on RECIST endpoints do not currently provide high-level evidence on its efficacy.